Pola distribusi spasial luas areal sertifikasi benih Padi Inbrida di Provinsi Banten - Okta Wulandono; Happy Suryati (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Rice is the main staple food in Indonesia, making increased rice production a key component of regional agricultural development and national food security. The use of certified high-quality rice seeds is a crucial factor in improving rice productivity. Therefore, understanding the spatial distribution patterns of certified inbred rice seed areas is essential for regional planning. This study aims to analyze the spatial distribution patterns of certified inbred rice seed areas in Banten Province. The dataset covers four planting seasons from 2022 to 2024 and includes seed classifications of Basic Seed (BD), Foundation Seed (BP), and Certified Seed (BR). The analytical methods employed include global and local spatial autocorrelation analyses using Moran’s Index and Local Indicators of Spatial Association (LISA). The results indicate that 33.33% of the observations exhibit strong spatial autocorrelation among sub-districts, while the remaining 66.67% display random spatial patterns. The spatial patterns vary across planting seasons and seed classes but are generally dominated by random distributions. LISA analysis identifies clustering patterns—High–High (HH), Low–Low (LL), Low–High (LH), and High–Low (HL)—primarily occurring in sub-districts within Lebak and Pandeglang Regencies. These findings provide valuable insights for regional agricultural development planning, particularly in determining priority locations for the expansion and distribution of certified high-quality rice seeds in Banten Province.